ISLAMIC RELIGIOUS VALUES REPRESENTED BY MAIN CHARACTERS AND PORTRAYED OF ISLAM WITHIN BUMI CINTA - Afifah, Wiwiek (Universitas Ahmad Dahlan, 2021)
Negative perceptions toward Islam are increasing because of the emergence of various issues in intolerance. On the other hand, an Islamic novel entitled Bumi Cintais full of virtuous capturing from the representation of the main character. Therefore, this study aims to find out the religious values and Islamic representations. The research method is inferential content analysis with the data obtained from the novel. The data procurement includes sampling and determination of the unit then validity of data is done by discussing them to the experts. The technique to analyze the data is classification, making meaning, and inference. Findings of this study are the spirit of seeking knowledge, honesty, discipline in worship, carry out all the religions commands, never surrender when getting problems, patient when facing temptations, stay away from haramfoods, sincere in giving aids, establishing fraternal relations with friends across religions and appeal to do good things. Therefore, from the whole analysis, it can be stated that Islam is a peaceful and tolerance religion that drove its adherents to become good people.